If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -11q = -2q + 10 Reorder the terms: -8 + -11q = 10 + -2q Solving -8 + -11q = 10 + -2q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2q' to each side of the equation. -8 + -11q + 2q = 10 + -2q + 2q Combine like terms: -11q + 2q = -9q -8 + -9q = 10 + -2q + 2q Combine like terms: -2q + 2q = 0 -8 + -9q = 10 + 0 -8 + -9q = 10 Add '8' to each side of the equation. -8 + 8 + -9q = 10 + 8 Combine like terms: -8 + 8 = 0 0 + -9q = 10 + 8 -9q = 10 + 8 Combine like terms: 10 + 8 = 18 -9q = 18 Divide each side by '-9'. q = -2 Simplifying q = -2
| (8x^2+6x-5)-(10x^2-9x+5)= | | -5(1-8v)=-5(1+3v) | | ((3x^2-1))/(4x(x-5))÷((3x^2-1)(x-1))/((x-5)) | | -9-15=12 | | 15m^2-23m=0 | | 162+17m=281 | | 6=0.03x-1.2 | | 24n-36=396 | | 2(-1)+5z=-2 | | 15*(7-7)+(5*2)=x | | -16+0.6x=8 | | 8n-6=-70 | | 6x+2(-3+4x)=1-x | | 8x-26=58+6x | | 3.14*25*8= | | x-3/7=9/6 | | 3.14+0.2x=5.34 | | 8y+10=58 | | 15*(7-7)+(5*2)= | | -1.4+0.02x=0.42 | | F=8/5(n-37) | | 21-0=14 | | 38.8-9.7g=-67.9 | | 1.1x-3=-6.3 | | 4=1/6x | | 3r-7r=4(3r+6)-8(1+r) | | 34n-208=336 | | 10/3=4/n | | -2000000-800000x=-3600000 | | 3.14*4*6= | | 5(-12-x)-10=10x-100 | | 2/3=r/7 |